Arabidopsis sucrose transporter 4 (AtSUC4) is involved in high sucrose-mediated inhibition of root elongation. Issue 1 (15th July 2022) - Liu, Siwen; Long, Jianmei; Zhang, Liding; Gao, Jiayu; Dong, Tiantian; Wang, Ying; Peng, Changcao
Abstract: Sucrose transporters (SUCs/SUTs) play crucial roles in apoplast transport and long-distance distribution of sucrose throughout the whole plant. However, whether and how the Arabidopsis AtSUC4 modulates sucrose import from apoplast to cytosol remains unclear. In the present study, we found that AtSUC4 protein was localized to the plasma membrane in the root. Expression of AtSUC4 in roots was gradually induced with the increasing sucrose concentrations (0%, 2%, 4% and 6%). When feeding high concentrations (4% and 6%) of sucrose, the primary root growth of seedling was inhibited. Interestingly, atsuc4 mutants exhibited longer primary root than the wild type under these conditions, indicating that atsuc4 mutants were less sensitive to excess sucrose. Moreover, the root of atsuc4 mutants accumulated less sucrose and abscisic acid (ABA) and more indole-3-acetic acid (IAA) on 4% and 6% sucrose supplementation. Transcriptomic analysis revealed that numerous genes associated with sugar transport and metabolism, as well as ABA signalling were down-regulated, whereas many IAA signaling-related genes were up-regulated in mutant plants relative to the wild type under 6% sucrose treatment. Collectively, our finding demonstrated that the deficiency of AtSUC4 reduced the inhibition of primary root growth under high sucrose condition, probably through reducing the sucrose transportation and metabolism, and subsequent alteration in IAA and ABA signalling.